2016
DOI: 10.1016/j.hpb.2016.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the risk of hepatocellular carcinoma in patients with prominently elevated liver stiffness measurements by FibroScan: a multicentre study

Abstract: This study shows an association between LSM at the upper extreme and HCC risk. Physicians may find this beneficial as a non-invasive dynamic approach to assessing HCC risk in cirrhosis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 32 publications
0
11
0
1
Order By: Relevance
“…Also, in the study of Adler et al [17] which was a retrospective observational study shows an association between liver stiffness measurements at the upper extreme and increasing HCC risk in patients with cirrhosis. LSM by Fibroscan allows stratification of HCC risk in a noninvasive and reliable way [26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Also, in the study of Adler et al [17] which was a retrospective observational study shows an association between liver stiffness measurements at the upper extreme and increasing HCC risk in patients with cirrhosis. LSM by Fibroscan allows stratification of HCC risk in a noninvasive and reliable way [26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 96%
“…Recently, the risk of liver cancer was assessed based on liver stiffness measured by Fibroscan among the European population [17]; however, in most reports, the risk of liver cancer has been indirectly assessed based on the value of cirrhosis as measured by Fibroscan; however, HCCassociated liver stiffness was not directly assessed [18].…”
Section: Introductionmentioning
confidence: 99%
“…The lower prediction performance and threshold in this study might be explained by the enrollment of decompensated cirrhosis patients and LS values determined at CVR in which confounding factors including inflammation were minimized. Our proposed cutoff was similar to the value of 20 kPa where in cirrhosis patients with the higher LS values, the greater risk was in HCC development . While achievement of the lowest LS is better, the thresholds of 21.5 and 11.6 kPa for cirrhosis patients with extreme high value and compensated advanced liver disease, respectively, might be the practical goal of potent NA therapy in clinical practice to reduce the risk of HCC development .…”
Section: Discussionmentioning
confidence: 63%
“…Therefore, several useful non-invasive methods for assessing liver fibrosis have been proposed and confirmed, such as FibroScan [27]. LSM by FibroScan had been recognized as an accurate method for assessing the stage of liver fibrosis in patients with chronic HBV infection [28], indicating values increasing as the liver disease progresses, and relating to HCC patients with cirrhotic background [29]. Jung et al [17] confirmed the high-preoperative LSM was associated with future science group www.futuremedicine.com significantly greater risk for recurrence of HCC, suggesting LSM can be a useful predictor of recurrence after curative resection of HCC.…”
Section: Discussionmentioning
confidence: 99%